2017
DOI: 10.1038/s41598-017-00510-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Two Massively Parallel Sequencing Platforms using 83 Single Nucleotide Polymorphisms for Human Identification

Abstract: The potential of Massively Parallel Sequencing (MPS) technology to vastly expand the capabilities of human identification led to the emergence of different MPS platforms that use forensically relevant genetic markers. Two of the MPS platforms that are currently available are the MiSeq® FGx™ Forensic Genomics System (Illumina) and the HID-Ion Personal Genome Machine (PGM)™ (Thermo Fisher Scientific). These are coupled with the ForenSeq™ DNA Signature Prep kit (Illumina) and the HID-Ion AmpliSeq™ Identity Panel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 21 publications
2
11
0
Order By: Relevance
“…Nevertheless, the ancestry inference was concordant for samples run on both systems. The results obtained in this study validate the inferences made on studies reported earlier for the PGM 9,2024,2632 in that the introduction of the automated workflow for higher throughput did not alter the predictions provided by the manufacturer’s plugin. With ever-increasing demands on the analyst, it is feasible that the S5 could be implemented to streamline operations, saving hours of labor to perform priority tasks.…”
Section: Discussionsupporting
confidence: 88%
“…Nevertheless, the ancestry inference was concordant for samples run on both systems. The results obtained in this study validate the inferences made on studies reported earlier for the PGM 9,2024,2632 in that the introduction of the automated workflow for higher throughput did not alter the predictions provided by the manufacturer’s plugin. With ever-increasing demands on the analyst, it is feasible that the S5 could be implemented to streamline operations, saving hours of labor to perform priority tasks.…”
Section: Discussionsupporting
confidence: 88%
“…The use of a threshold for the "locus call" (e.g., its genotyping) has been debated from the very beginning of the application of PCR-MPS technologies in Forensic Genetics, and a minimum of 20 x has been suggested as a reliable threshold [12]. To date, a wide range of thresholds, from 6 x to 200 x, have been used in different studies characterizing the Precision ID Identity Panel [12][13][14]23,[26][27][28] as well other SNP-based methods [39][40][41]. In the present study, the definition of this threshold has been empirically defined as follows.…”
Section: Threshold For Locus Callmentioning
confidence: 99%
“…Given the reported higher sensitivity and specificity of NGS methods for IGH and TCR clonality testing, we decided to move from a method that used PCR fragment analysis by capillary electrophoresis (Invivoscribe, Inc) to an NGS-based method. Here we describe how we validated the NGS LymphoTrack assays [ 9 , 10 , 22 ] (Invivoscribe, Inc) with the Ion Torrent S5 sequencing instrument, which employs a different sequencing chemistry than the Illumina platforms [ 23 , 24 ] and has not been previously reported for use with NGS clonality studies to our knowledge. We also discuss the pitfalls in comparing to other molecular methodologies and to clinical measurements of disease and in interpreting results.…”
Section: Introductionmentioning
confidence: 99%